(untitled) (Fiep Bulletin - online, 2015)
Raman spectroscopy has been largely used in biology and biochemistry as a tool to study the structures and functional dynamics of important molecules, as for example the study of the presence of biochemical substances in the blood (BAYDEN e McNAUGHTON, 2001; PILOTTO et al., 2001; SATO et al., 2001;). Exercise has some immediate effects on the protein metabolism. Branched chain amino acids’ oxidation can be an important source of energy to the muscles during anaerobic exercises. The presence of the alanine in the blood may indicate the use of amino acids for obtaining energy. The goal of this paper is to compare the presence of alanine in the blood before and after a high-intensity anaerobic exercise, using FT-Raman spectroscopy. It concludes that FT-Raman spectroscopy is efficient to determine and increase in the alanine concentration in the blood.